Probing the secondary structure of bovine serum albumin during heat-induced denaturation using mid-infrared fiberoptic sensors - Lu, Rui; Li, Wen-Wei; Katzir, Abraham; Raichlin, Yosef; Yu, Han-Qing; Mizaikoff, Boris (Analyst (London), 2015)
Attenuated total reflection Fourier transform infrared (ATR-FTIR) spectroscopy using a special waveguide based on a silver halide fiber was used for probing the heat-induced secondary structure and conformation changes of bovine serum albumin (BSA). From the secondary derivative and the curve fitting of the obtained ATR-FTIR spectra, the changes of the BSA secondary structure with temperature were clearly identified. Two different thermal denaturation temperature ranges ( i.e. , 50-52 and 80-82 °C, at which a change of the protein structure occurred) were determined, while only one denaturation temperature was previously identified via classical FTIR measurements. Additionally, taking advantage of two-dimensional correlation spectroscopy more detailed information on changes of the protein secondary structure was revealed. The developed method facilitates in situ , sensitive, and more in-depth probing of protein secondary structures, which represents a significant advancement compared to conventional characterization methods. Planar silver halide fiberoptic sensors were used for the first time for studying the mechanism of heating induced bovine serum albumin (BSA) denaturation by deconvoluted infrared attenuated total reflection (IR-ATR) spectra, and two-dimensional correlation spectroscopy (2D-CoS).